Formal insurance, risk sharing, and the dynamics of other-regarding preferences - Hanna Freudenreich; Marcela Ibanez; Stephan Dietrich; Oliver Musshoff (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2018)
In the absence of formal financial markets many poor households rely on the mutual exchange of transfers within informal risk sharing networks to protect themselves against adverse events. In this paper we present a model that explains the impact of formal insurance on informal risk sharing and, subsequently, the dynamics of other-regarding preferences. We test the predictions of the model using a solidarity game with rural households in Mexico. Consistent with the model predictions, we find that when shocks are collective, there is a crowding-out effect on transfers and a decrease in trust on insured participants. However, when shocks are idiosyncratic, we fail to confirm the predictions of the model. Transfers to non-insured members are significantly higher when insurance is available to some of the network members than in a control treatment when insurance is not available. This unexpected crowding-in effect on transfers leads to an increase in trust among non-insured participants. These findings suggest that there is a need to find optimal insurance designs that minimizes the crowding-out effect of formal insurance on informal risk sharing and other-regarding preferences.
Keywords: 330